(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main purpose of the grounding system is to protect human, electrical appliance and building from electrical shock due to lightning or another form of electricity that hazardous. Therefore, to achieve this goal, the fundamental part must be taken into account. In this paper, a different 3-D orientation of concrete has been designed using Comsol software to analyze the performance of the electric potential of the injected impulse in different cases and position of grounding system modelled. In this study, few grounding systems was modelled, which consist of Full concrete, Three-quarter concrete, Half concrete and A quarter concrete to analyse the electric potential of the injected lightning impulse current to the performance of the grounding system modelled. From the result obtained, full concrete was chosen as the best orientation of concrete to be employed at the grounding site. This is because, full concrete has the lowest electric potential value compared to the other cases and position of concrete..